A decellularized porcine pulmonary valved conduit embedded with gelatin. Issue 9 (28th April 2021) - Wan, Juyi; Zhong, Xiaolin; Xu, Zhiwei; Gong, Da; Li, Diankun; Xin, Zhifei; Ma, Xiaolong; Li, Wenbin
Abstract: To prepare a tissue‐engineered pulmonary valved conduit (PVC) with good tensile strength and biocompatibility. Sixty adult porcine PVCs were used to determine the optimal decellularization time. Five juvenile porcine decellularized PVCs and five juvenile porcine crosslinked PVCs were subsequently prepared according to the optimized decellularization and crosslinking methods. All PVCs were implanted into juvenile sheep for 8 months and then were harvested for staining. With a low concentration of detergent (0.25% Triton X‐100+0.25% sodium deoxycholate), the decellularization effect on porcine PVCs was complete by 24 hours, and there was minimal damage to the matrix. Gelatin embedding and 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide (EDC) crosslinking improved the biomechanical properties of decellularized PVCs and reduced their immunogenicity. After implantation, the diameter and thickness of the PVCs in the decellularized and crosslinked groups increased significantly. In both groups, the conduits were unobstructed, with soft and smooth inner walls and without thrombosis, ulceration or neoplasia. The valves slightly degenerated with mild to moderate regurgitation. CD31‐positive endothelial cells were visible on the inner surface of the conduits and valves. Scattered smooth muscle actin‐positive cells were found in the middle layer of the conduit. The percentage of CD4‐ and CD68‐positive cells and the calcium content were highest in decellularized porcine PVCs and lowest in ovine PVCs. The percentage of the matrix that was laminin‐positive in decellularized and crosslinked porcine PVCs was lower than it was in ovine PVCs. Gelatin‐embedded and EDC‐crosslinked porcine PVCs can be "hosted" in sheep, with good biocompatibility, growth potential, and reduced calcification. Abstract : Gelatin‐embedded and 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide‐crosslinked decellularized porcine pulmonary valved conduits can be "hosted" in sheep, with good biocompatibility, growth potential and reduced calcification.